COVID-19 Infection During Pregnancy Induces Differential Gene Expression in Human Cord Blood Cells From Term Neonates - Gayen nee' Betal, Suhita; Urday, Pedro; Al-Kouatly, Huda B.; Solarin, Kolawole; Chan, Joanna S. Y.; Addya, Sankar; Boelig, Rupsa C.; Aghai, Zubair H. (Frontiers in Pediatrics, 2022)
Background: The COVID-19 pandemic continues worldwide with fluctuating case numbers in the United States. This pandemic has affected every segment of the population with more recent hospitalizations in the pediatric population. Vertical transmission of COVID-19 is uncommon, but reports show that there are thrombotic, vascular, and inflammatory changes in the placenta to which neonates are prenatally exposed. Individuals exposed in utero to influenza during the 1918 pandemic had increased risk for heart disease, kidney disease, diabetes, stomach disease and hypertension. Early exposure of COVID-19 during fetal life may lead to altered gene expression with potential long-term consequences. Objective: To determine if gene expression is altered in cord blood cells from term neonates who were exposed to COVID-19 during pregnancy and to identify potential gene pathways impacted by maternal COVID-19. Methods: Cord blood was collected from 16 term neonates (8 exposed to COVID-19 during pregnancy and 8 controls without exposure to COVID-19). Genome-wide gene expression screening was performed using Human Clariom S gene chips on total RNA extracted from cord blood cells. Results: We identified 510 differentially expressed genes (374 genes up-regulated, 136 genes down-regulated, fold change ≥ 1.5, p-value ≤ 0.05) in cord blood cells associated with exposure to COVID-19 during pregnancy. Ingenuity Pathway Analysis identified important canonical pathways associated with diseases such as cardiovascular disease, hematological disease, embryonic cancer and cellular development. Tox functions related to cardiotoxicity, hepatotoxicity and nephrotoxicity were also altered after exposure to COVID-19 during pregnancy. Conclusions: Exposure to COVID-19 during pregnancy induces differential gene expression in cord blood cells. The differentially expressed genes may potentially contribute to cardiac, hepatic, renal and immunological disorders in offspring exposed to COVID-19 during pregnancy. These findings lead to a further understanding of the effects of COVID-19 exposure at an early stage of life and its potential long-term consequences as well as therapeutic targets.